Correction to Construction of Panoramic Image Mosaics with Global and Local Alignment - Shum, Harry; Szeliski, Rick (International Journal of Computer Vision, 2002)
An important element of this framework, which we exploit, is to perform the motion estimation between the current new input image and a warped (resampled) version of the mosaic. This allows us to estimate only incremental deformations of images (or equivalently, instantaneous motion), which greatly simplifies the computation of the gradients and Hessians required in our gradient descent algorithm (e.g., compare the Hessians computed below with those presented in Szeliski, 1996). Thus, to register two images I0(x) and I1(x′), where x′ is computed using some parametric motion model m, i.e., x′ = f(x; m), we first compute the warped image...